Queering recovery: A proposed model for LGBTQ+-affirmative relapse prevention - Chaney, Michael P. (Journal of addictions & offender counseling, 2024)
Professional counseling literature pertaining to substance use counseling for LGBTQ+ communities is scant. One such exclusion is relapse prevention for LGBTQ+ clients. To meet this gap, this paper explored LGBTQ+-specific factors that contribute to the development and maintenance of substance use and the risk of relapse once in recovery. We extend Witkiewitz and Marlatt's Dynamic Model of Relapse by identifying and integrating examples of LGBTQ+-specific tonic and phasic elements that influence relapse. Based on these postulations, an LGBTQ+-affirmative model of relapse prevention is introduced. Implications for research and pedagogy are proposed.